2023
DOI: 10.1177/00315125231222398
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Academic Buoyancy and Self-Efficacy in Predicting Teachers’ Work Engagement: A Case of Chinese English as a Foreign Language Teachers

Ran Zhi,
Yongxiang Wang,
Ali Derakhshan

Abstract: A plethora of scientific evidence has pinpointed that teaching English as a foreign or second language (EFL) is difficult, challenging, and emotionally burdensome. Nevertheless, most English language teachers remain committed to the teaching profession and actively engage in the instructional environment. This has inspired several scholars worldwide to explore what personal, emotional, and psychological factors motivate English language teachers to engage enthusiastically in their workplace. While a large body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…Moreover, most existing research focuses on pre-service teachers (e.g., Alrashidi, 2022;Hoang & Wyatt, 2021;Li et al, 2023). Given the significant difference between pre-service and in-service language teachers (Horwitz, 1996), it is necessary to conduct more research on in-service FL teachers (e.g., Liu et al, 2022;Zhi et al, 2023). In view of these gaps, this study aimed to explore the relationships among Chinese pre-university EFL teachers' TFLA, TA and TSE.…”
Section: Research Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, most existing research focuses on pre-service teachers (e.g., Alrashidi, 2022;Hoang & Wyatt, 2021;Li et al, 2023). Given the significant difference between pre-service and in-service language teachers (Horwitz, 1996), it is necessary to conduct more research on in-service FL teachers (e.g., Liu et al, 2022;Zhi et al, 2023). In view of these gaps, this study aimed to explore the relationships among Chinese pre-university EFL teachers' TFLA, TA and TSE.…”
Section: Research Questionsmentioning
confidence: 99%
“…Empirical studies on FL teachers' self-efficacy have been conducted through questionnaires, interviews, class observations and so on (e.g. Deng et al, 2022;Hoang & Wyatt, 2021;Zhi et al, 2023). These studies have identified several factors that influence language teachers' self-efficacy, such as affective states (Phan & Locke, 2015), previous experiences (Hoang & Wyatt, 2021), language proficiency (Choi & Lee, 2016), emotional intelligence (Moafian & Ghanizadeh, 2009), emotion regulation (Deng et al, 2022), and so on.…”
Section: Tsementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, emotional intelligence plays a pivotal role in moderating self-efficacy and burnout. On the one hand, some studies demonstrated that teachers' emotional intelligence is positively associated with self-efficacy [ [54] , [55] ]. Anwar et al [ 56 ] carried out research examining the mediating role of emotional intelligence in enhancing the teaching effectiveness of foreign language educators.…”
Section: Literature Reviewmentioning
confidence: 99%